2021
DOI: 10.1136/heartjnl-2020-318860
|View full text |Cite
|
Sign up to set email alerts
|

Addition of cystatin C predicts cardiovascular death better than creatinine in intensive care

Abstract: ObjectiveDecreased kidney function increases cardiovascular risk and predicts poor survival. Estimated glomerular filtration rate (eGFR) by creatinine may theoretically be less accurate in the critically ill. This observational study compares long-term cardiovascular mortality risk by the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine equation; Caucasian, Asian, paediatric and adult cohort (CAPA) cystatin C equation and the CKD-EPI combined creatinine/cystatin C equation.MethodsThe nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, we found that eGFR discrepancy is associated with significantly higher 30-day mortality even after adjustment for demographics, comorbidities, baseline laboratory studies, and medication use. Although higher serum creatinine and cystatin C have each been shown to be associated with increased mortality in multiple clinical settings, [49][50][51][52][53][54] our finding suggests that discrepancy between creatinine and cystatin C, in addition to the absolute values of either marker, adds further information and potentially serves as an independent predictor of death.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, we found that eGFR discrepancy is associated with significantly higher 30-day mortality even after adjustment for demographics, comorbidities, baseline laboratory studies, and medication use. Although higher serum creatinine and cystatin C have each been shown to be associated with increased mortality in multiple clinical settings, [49][50][51][52][53][54] our finding suggests that discrepancy between creatinine and cystatin C, in addition to the absolute values of either marker, adds further information and potentially serves as an independent predictor of death.…”
Section: Discussionmentioning
confidence: 70%
“…It is worth highlighting that SEM 2 and eGFRcys outperformed eGFRcrecys in CVD risk prediction. A previous study reported that a combination of eGFRcre- and eGFRcys-based categories could improve prediction of CVD mortality in intensive care [ 37 ], but this may be a very different context compared to a general population situation, where most individuals are healthy or have a low burden of disease. The question remains as to why the performance of a single biomarker, eGFRcys, was not much inferior to SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Cystatine C has a predictive value in COVID-19 [ 13 , 34 , 65 , 66 ] and also in ICU patients in general [ 14 , 21 , 67 ]. Cystatin C has the drawback of being affected by corticosteroids [ 15 , 16 , 17 ], but not by CRP [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, dexamethasone was identified as being able to improve outcomes in hospitalized COVID-19 patients needing supplemental oxygen [ 19 , 20 ]. This implies a potential for underestimating eGFR when using the cystatine C CAPA (Caucasian, Asian, Pediatric, and Adult) equation [ 21 ] in the COVID-19 cohort. The effect of dexamethasone on eGFR CAPA in COVID-19 has, to the best of our knowledge, not previously been evaluated.…”
Section: Introductionmentioning
confidence: 99%